OXPHOS remodeling in high-grade prostate cancer involves mtDNA mutations and increased succinate oxidation - Bernd Schöpf (Nature Portfolio, 2020)
The re-wiring of the metabolic machinery is a common feature in cancer. Here, the authors show, using paired normal and prostate cancer samples that the cancer samples exhibit a shift to succinate respiration, which is associated with elevated levels of mitochondrial DNA mutations.